Beta Alpha Psi, From Omega to Zeta Omega: The Making of a Comprehensive Accounting Fraternity (Book). - Brief, Richard P.; Burns, Thomas J. (The Accounting Review, 1988)
Reviews the book "Beta Alpha Psi, From Omega to Zeta Omega: The Making of a Comprehensive Accounting Fraternity, 1946-1984" by Terry K. Sheldahl.